Impact of Social Factors and Peer Tutoring on Writing Proficiency of EFL Learners in Pakistan at Secondary School Level (Journal of Social Sciences Review, 2023)
This study investigated the impact of social factors and peer tutoring on EFL students’ academic performance. In this research work, peer tutoring strategy was used to examine its effectiveness. Three dimensions of peer tutoring ‘reciprocal peer tutoring, class-wide peer tutoring and cross-age peer tutoring’ were used. The objectives of the study were to find the effectiveness of social factors and peer tutoring on writing fluency and accuracy of EFL learners and to investigate the advantages and disadvantages of peer tutoring in EFL writing skills. The population of the study consisted of the students of 9th and 10th grade from a private school in District Mansehra. A sample of 90 students was taken randomly and these students were divided into control group and experimental group. Quasi experimental design, “Pretest-Posttest Nonequivalent Groups Design” was used to collect data. Among 60 students in experimental group, students who achieved above average marks, were selected as peers. Then posttest was conducted to find the effectiveness of peer tutoring. The data was analyzed through computer software SPSS version 21. The results showed a significant difference in students’ achievement in writing skills in experimental group. It was recommended to practice this technique in classroom to achieve academic skills.
Keywords: Social Factors; Peers; Learning; Proficiency; Experimental; Control; Group; Student